PERANCANGAN KEMASAN “BATIAH RANAH MINANG” MAKANAN KHAS PAYAKUMBUH - Deri febrian; M Nasrul Kamal; Riri Trinanda (Universitas Negeri Padang, 2021)
Writing this final project aims to design a business Buk Epi Sofinar which is located at Keluran Padang Tinggi Piliang, Payakumbuh City. Buk Epi has a business called Batiah Ranah Minang. Consumers do not know and understand the superiority of the product and the current identity of Batiah Ranah Minang is not optimal, making Buk Epi's business less noticed by consumers. Purpose of packaging design as a print media that functions product identity in an informative and communicative manner for consumer satisfaction and to increase product safety.The Glass Box method is used in designing, collecting data through observation, interviews and documentation from the owner. The method of SWOT data analysis as a problem solving by raising the advantages of getting the right layout, typography, and colors for Batiah Ranah Minang.The design of Batiah Ranah Minang business packaging design in Payakumbuh, can attract the attention of buyers and increase the existence of food businesses in the city of Payakumbuh. The addition of media such as X-banners, business cards, t-shirts, aprons, stickers, paper bags and mugs aims to support the main packaging media.Keywords: Packaging , Batiah Ranah Minang , Design